Detection of acid sphingomyelinase in human saliva and its advantages in the diagnosis of Niemann-Pick disease type B - Alicia Giner-Ayala; Celia Juana Angaroni; Raquel Dodelson de Kremer; Lidia Dora Martínez (Journal of Clinical and Scientific Research, 2021)
Background: Niemann-Pick disease type B is an autosomal recessive lysosomal storage disorder caused by a deficiency of acid sphingomyelinase (ASM) coded by SMPD1 gene. Diagnostic assays for this enzyme were developed using fibroblasts, leukocytes, plasma and dry blood spots, however, there are no expression studies in saliva in the literature, so far. Saliva is a biofluid used to analyze the health/disease condition of an individual. Methods: We standardized a fluorometric method to determine ASM activity in human saliva of control subjects and in one NPD-B patient. Results: ASM activity was detected in all saliva samples. The range of ASM in saliva of 28 control subjects was 4.5 - 70.4 with an average of 26.93 ± 15.7 nmol/17h/mg of protein. Values in plasma were significantly lower, a 0.056- 3.2 range, with an average of 0.85 ± 0.7 nmol/17h/mg of protein. There was no correlation between saliva and plasma samples (R2= 0.001). ASM was markedly deficient in saliva activity of (0.09 nmol/17h/ mg of protein) as well as in the leukocyte pellet (0.125 nmol/17h/mg protein) and in the plasma (0.68 nmol/17h) of the NPD-B patient. Conclusion: Our observations indicate that saliva could be an alternative biofluid to plasma and to leucocytes to measure ASM activity, representing a non-invasive, easy-collection diagnostic means, which would allow the identification and characterization of these entities.